How was the quadratic formula obtained.

We want a solution to ax^2+bx+c=0. Complete the square to get a[(x+b/2a)^2 -(b^2)/(4a^2)]+c=0. Expalding brackets and rearanging gets a(x+b/2a)^2=(b^2)/4a -c. Divide by a to get (x+b/2a)^2= b^2/4a^2 -c/a=(b^2-4ac)/4a^2. Then root each side tot get (x+b/2a)=+-(root(b^2-4ac))/2a. Then simply move over the b/2a to get x=-b/2a+- (root(b^2-4ac))/2a=(-b+-(root(b^2-4ac)))/2a.

Answered by Jon H. Maths tutor

3061 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given y = 9x + 1/x, find the values of x such that dy/dx=0


Mechanics 1: How do you calculate the magnitude of impulse exerted on a particle during a collision of two particles, given their masses and velocities.


Solve, correct to 2 decimal places, the equation cot(2x)=3 for 0°<x<180°


Water is flowing into a rightcircular cone at the rate r (volume of water per unit time). The cone has radius a, altitude b and the vertex or "tip" is pointing downwards. Find the rate at which the surface is rising when the depth of the water is y.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences